Peirces account of assertion - Iglesias, Jaime Orlando Alfaro (2016)
One usually makes assertions by means of uttering indicative sentences like It is raining. However, not every utterance of an indicative sentence is an assertion. For example, in uttering I will be back tomorrow, one might be making a promise. What is to make an assertion? C.S. Peirce held the view that to assert a proposition is to make oneself responsible for its truth (CP 5.543). In this thesis, I interpret Peirces view of assertion and I evaluate Peirces reasons for holding it. I begin by reconstructing and assessing Peirces case for such view as it appears in (EP 2.140, 1903), (EP 2.312-313, 1904), and (CP 5.546, 1908). Then, I continue by elaborating on three aspects of Peirces view of assertion, namely, assertion as an act involving a certain kind of responsibility, the proposition as what is asserted, and responsibility for truth as a responsibility to give reasons. With respect to these three aspects, I argue for the following claims: (1) Peirce construed the responsibility involved in asserting as a moral responsibility; (2) Peirce held that propositions are types; and (3) Peirce was committed to a dialogical interpretation of responsibility to give reasons. Finally, I end by presenting two objections to Peirces view of assertion and its corresponding replies. I conclude that Peirces account of assertion is a valuable contribution to the philosophical debate on assertion.